Anti-Poverty Policies and the Adoption of Bill 112 in Quebec: A Change of Path? - Dufour, Pascale (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2012)
In this paper, we address anti-poverty policies in Quebec and especially the adoption of Bill 112 in December 2002. We argue that apart from structural elements specific to the Quebec context, without the popular mobilisation initiated by the Collectif pour une loi sur l'élimination de la pauvreté, Bill 112 would not have been developed or passed into law. We show first how social actors have created a movement that changed the conditions of public action towards poverty, analysing the particular political opportunity structure of the time period (1995-2002) favourable to the Collectif and two internal dimensions of the movement: its efficient strategy, and the fact that poor people themselves were at the forefront of the mobilisation. We then argue that these changes are not equivalent for all poor persons in terms of material gains. We finish by suggesting that the most important change is cognitive. All in all, Bill 112 should be seen as an exception in the political treatment of poverty; but a moment that has only slightly changed the rules of the game and the possibilities for future state actions.Dans cet article, nous traitons des politiques anti-pauvreté au Québec et spécialement de l'adoption de la Loi 112 en décembre 2002. Nous soutenons que mis à part des éléments structurels spécifiques au contexte québécois, sans la mobilisation populaire initiée par le Collectif pour une loi sur l'élimination de la pauvreté, la Loi 112 n'aurait pas étéproposée ou adoptée. Nous montrons, dans un premier temps, comment les acteurs sociaux ont créé un mouvement qui a changé les conditions de l'action publique envers lapauvreté, en analysant la structure d'opportunité politique de la période (1995-2002) favorable au Collectif ainsi que deux dimensions internes du mouvement: sa stratégie efficace et le fait que les personnes pauvres elles-mêmes étaient à l'avant-plan des mobilisations. Nous soutenons, ensuite, que ces changements ne sont pas identiques pour toutes les personnes pauvres, en termes de gains matériels et nousterminons en suggérant que le changement le plus important est surtout cognitif. Tout bien considéré, la Loi 112 doit être vu comme un moment d'exception dans le traitement politique de la pauvreté; mais un moment qui changé les règles du jeu (même marginalement) et les possibilités de l'action publiquefuture.